Recurrent pericarditis in a patient with Bardet–Biedl syndrome: A case report - Mauro, Angela; Casini, Francesca; Congedo, Emanuele Chittano; L’assainato, Sara; Pinto, Francesca; Ansuini, Valentina; Mascolo, Ruggiero; Pedroli, Alice; Bernardo, Luca (Frontiers in Pediatrics, 2022)
Bardet–Biedl syndrome is a rare autosomal recessive disorder characterized by rod-cone dystrophy, renal dysfunction, obesity, learning difficulties, hypogonadism, polydactyl, and many other minor features that can affect the cardiovascular, locomotive, neurological, and endocrine systems. We report the case of a 16-year-old boy affected by Bardet–Biedl syndrome who presented with recurrent pericarditis with an optimal response to treatment with Anakinra. To our knowledge, this is the first description of an association between Bardet–Biedl syndrome and recurrent pericarditis.